Ten simple rules for working with high resolution remote sensing data - Mahood, Adam L.; Joseph, Maxwell B.; Spiers, Anna I.; Koontz, Michael J.; Ilangakoon, Nayani; Solvik, Kylen K.; Quarderer, Nathan; McGlinchy, Joe; Scholl, Victoria M.; St. Denis, Lise A.; Nagy, Chelsea; Braswell, Anna; et al. (Peer Community Journal, 2023)
Researchers in Earth and environmental science can extract incredible value from high- resolution (sub-meter, sub-hourly or hyper-spectral) remote sensing data, but these data can be difficult to use. Correct, appropriate and competent use of such data requires skills from remote sensing and the data sciences that are rarely taught together. In practice, many researchers teach themselves how to use high-resolution remote sensing data with ad hoc trial and error processes, often resulting in wasted effort and resources. In order to implement a consistent strategy, we outline ten rules with examples from Earth and environmental science to help academic researchers and professionals in industry work more effectively and competently with high-resolution data.